2017
DOI: 10.12998/wjcc.v5.i7.303
|View full text |Cite
|
Sign up to set email alerts
|

Is dengue emerging as important cause of acute liver failure in endemic regions?

Abstract: Dengue virus infection continues to be major public health problem in large part of world. The epidemiology of dengue viral infection is becoming increasingly complex and has substantially changed over almost past six decades not only in terms of prevalent strains and geographical locations but also in terms of disease severity and atypical presentations. Though liver is the most common organ affected but is generally asymptomatic. We present a case of infant with severe dengue who died of fulminant hepatic fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…Confirming the link between liver damage and certain metabolites, Cui et al [25,93] found elevated liver transaminases correlated with elevated bile acids. Acceptance that DENVs cause liver damage is gaining traction [107,108], though the sensitivity of metabolomic findings suggests earlier mild damage than previously appreciated.…”
Section: Denvmentioning
confidence: 99%
“…Confirming the link between liver damage and certain metabolites, Cui et al [25,93] found elevated liver transaminases correlated with elevated bile acids. Acceptance that DENVs cause liver damage is gaining traction [107,108], though the sensitivity of metabolomic findings suggests earlier mild damage than previously appreciated.…”
Section: Denvmentioning
confidence: 99%
“…This is a rare condition with high mortality, 53 and has been described in dengue since 1980. 54,55 Ultimately, HLH was shown to be a form of presentation in children with severe dengue, who more frequently showed splenomegaly, bacterial coinfection, anemia, transaminase levels >1000 U/L and LDH >1000 U/L. These patients also presented with more multiorgan involvement, as evidenced by a higher proportion of subjects with myocarditis and hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Así mismo, el paciente desarrolló falla hepática aguda (FHA) por dengue, patología que aunque es infrecuente tiene alta mortalidad, no sólo por alteración en las funciones de síntesis y de detoxificación, sino porque refleja una respuesta inflamatoria severa frente a la infección (6). En la práctica, aparte del uso de medicamentos y algunos virus hepatotropos, el dengue debería ser considerado como un diagnóstico diferencial de FHA en los países de alta endemicidad como Colombia, por el incremento considerable de su prevalencia en las últimas décadas debido a las malas condiciones de higiene y el cambio climático (2,7).…”
Section: Discussionunclassified